Évaluation de la prescription et de l’utilisation des benzodiazépines dans la ville de Sidi Bel-Abbès - Derouicha Matmour; Mounia Medjeber; Yassine Merad (Journal de la Faculté de Médecine d'Oran)
Abstract Introduction-A high consumption of benzodiazepines (BZDs) has been noticed sometimes outside the rules of prescription recommendations, which makes their consumption a major public health problem. The present study aimed to evaluate the prescription and use of BZDs in Sidi Bel-Abbès city. Methods-: This was a descriptive cross-sectional study carried out from February 01st, 2018 to June 30th, 2018 evaluating the prescription and use of BZDs in of Sidi Bel-Abbès by means of a questionnaire distributed to patients from the psychiatric hospital, the CHU psychiatry department and community pharmacists. The primary endpoint was the assessment of the prescription and use of BZDs in this city. Data entry and analysis were performed using SPSS software. Results-A total of 353 patients treated with at least one BZD were included, including 178 men. The prescription rate of BZDs was 1.10, young people (59.77%) and married people (60.34%) were the privileged consumers. The prescription was the prerogative of psychiatrists, in monotherapy (07.42%), the molecule most frequently prescribed was Bromazepam (31.07%) and night intake was the most important (49.01%). BZDs were used to combat insomnia (25.21%), anxiety (16.43%), for a period of more than a year (57.79%). Conclusion-The prescription and use of BZDs in Sidi Bel-Abbès has proven to be important. Insomnia and anxiety were the main reasons for their use, and Bromazepam was the most molecule frequently used.